The challenge of comprehensively mapping children's health in a nation-wide health survey: Design of the German KiGGS-Study - Schlack Robert; Schenk Liane; Scheidt-Nave Christa; Rosario Angelika; Neuhauser Hannelore; Mensink Gert BM; Lange Michael; Knopf Hiltraud; Kahl Heidrun; Ellert Ute; Dölle Rüdiger; Schlaud Martin; et al. (BMC, 2008)
Abstract Background From May 2003 to May 2006, the Robert Koch Institute conducted the German Health Interview and Examination Survey for Children and Adolescents (KiGGS). Aim of this first nationwide interview and examination survey was to collect comprehensive data on the health status of children and adolescents aged 0 to 17 years. Methods/Design Participants were enrolled in two steps: first, 167 study locations (sample points) were chosen; second, subjects were randomly selected from the official registers of local residents. The survey involved questionnaires filled in by parents and parallel questionnaires for children aged 11 years and older, physical examinations and tests, and a computer assisted personal interview performed by study physicians. A wide range of blood and urine testing was carried out at central laboratories. A total of 17 641 children and adolescents were surveyed - 8985 boys and 8656 girls. The proportion of sample neutral drop-outs was 5.3%. The response rate was 66.6%. Discussion The response rate showed little variation between age groups and sexes, but marked variation between resident aliens and Germans, between inhabitants of cities with a population of 100 000 or more and sample points with fewer inhabitants, as well as between the old West German states and the former East German states. By analysing the short non-responder questionnaires it was proven that the collected data give comprehensive and nationally representative evidence on the health status of children and adolescents aged 0 to 17 years.